2019
DOI: 10.1089/tmj.2017.0133
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical Assessment Using Telemedicine Technology: Impact on Efficiency, Effectiveness, and Patient Experience of Care

Abstract: PAT utilizing telemedicine reduced overall patient time in the PAT and improved patient satisfaction without increasing the operative case cancellation rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
1
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 11 publications
2
83
1
14
Order By: Relevance
“…This retrospective study represents the largest published case series of telemedicine for preoperative evaluation in a metropolitan, urban, health system. Whereas we used telemedicine in place of in-person visits, in a comparable study, Mullen-Fortino et al 14 used telemedicine consultations inseries and in conjunction with in-person consultation. Additionally, we discuss issues related to patient savings, satisfaction, and cancellation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This retrospective study represents the largest published case series of telemedicine for preoperative evaluation in a metropolitan, urban, health system. Whereas we used telemedicine in place of in-person visits, in a comparable study, Mullen-Fortino et al 14 used telemedicine consultations inseries and in conjunction with in-person consultation. Additionally, we discuss issues related to patient savings, satisfaction, and cancellation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other studies, 9 , 12 , 13 patients rated telemedicine consultations favorably. Mullen-Fortino et al 14 showed that 97.5% of patients preferred telemedicine-based applications for anesthesia presurgical evaluation. Of the 131 respondents, 129 of131 participants (98%) “agreed” or “strongly agreed” that they were satisfied with a video preoperative consultation, with 120 of131 patients (92%) reporting that they “agreed” or “strongly agreed” that they preferred these visits in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were limited reports of the use of telehealth as a full replacement for face-to-face PAT, but these reports indicated that patients had shorter visits, few or no case cancellations, accurate clinical evaluation as compared to face-to-face, and high rates of both provider and patient satisfaction. 16 , 17 Despite the convenience and time-savings, there are certain aspects of PAT that cannot currently be resolved via virtual visit such as direct airway evaluation, laboratory studies, or more sophisticated electrocardiography. More sophisticated remote patient monitoring and increasingly higher quality cameras and videos on mobile devices may address some of these gaps.…”
Section: Preadmission and Postsurgical Impactsmentioning
confidence: 99%
“…Despite, the positive experiences that have previously been reported, regarding significant improvements in the efficiency of patient care by telemedicine programs in other regions [10,18,19], evidence in Chilean teleneurology programs remain unpublished. Moreover, since the implementation of the Teleneurology Program, a seemingly decreasing trend of the number of patients waiting for their first consultation appears to be in contrast with the increasing trend in this figure for the rest of the country.…”
Section: Introductionmentioning
confidence: 99%